1993
DOI: 10.1007/bf00018808
|View full text |Cite
|
Sign up to set email alerts
|

Saline lakes of the Paroo, inland New South Wales, Australia

Abstract: Twenty-five lakes from fresh to crystallizing brine in the semi-desert of northwestern New South Wales, Australia, were studied regularly for 27 months. The lakes are small, shallow and ephemeral. Chemically waters are mainly of the NaCl type. Seventy-four species of invertebrate occur in saline waters (> 3 g l-') with crustaceans such as Parartemia minuta, Apocyclops dengizicus, Daphniopsis queenslandensis, Diacypris spp. and Reticypris spp. dominant, particularly at higher salinities. The insects Tanytarsus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 24 publications
4
77
0
Order By: Relevance
“…In our study, zooplankton species richness demonstrated to be negatively related to salinity (Rho = x 0.491, P = 0.015), a pattern that has been widely descripted by previous authors (Timms, 1993;Cooper and Wissel, 2012), since a few number of species are able to tolerate an increase in salt concentration. The presence of the genera Brachionus, Cephalodella and Boeckella in HH and MH lakes is consistent with previous founding, since these genera are greatly adapted to high salt concentrations (Derry et al, 2003;Battauz et al, 2013).…”
Section: Discussion Salinity and Altitude As Controlling Factors Of Psupporting
confidence: 80%
See 1 more Smart Citation
“…In our study, zooplankton species richness demonstrated to be negatively related to salinity (Rho = x 0.491, P = 0.015), a pattern that has been widely descripted by previous authors (Timms, 1993;Cooper and Wissel, 2012), since a few number of species are able to tolerate an increase in salt concentration. The presence of the genera Brachionus, Cephalodella and Boeckella in HH and MH lakes is consistent with previous founding, since these genera are greatly adapted to high salt concentrations (Derry et al, 2003;Battauz et al, 2013).…”
Section: Discussion Salinity and Altitude As Controlling Factors Of Psupporting
confidence: 80%
“…In salt lakes where plankton is adapted to high ionic concentrations, factors such as habitat stability, predation and resource availability could be more important in the structuration of this community (Timms, 1993;Cooper and Wissel, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Shiel (e.g. Timms, 1993), including lakes of the far southwest coast of Western Australia, where maximum salinity was <3 g L 1 (Edward et ai, 1994). In this survey, richness of the two assemblages that showed most sensitivity to salt tended to be greatest in higher rainfall belts, suggesting that the assertion of Horwitz (1997) that salt sensitive species in the Warren region are most likely to occur along the higher rainfall coast applies at a larger and more general scale to south-west Western Australia as a whole.…”
Section: Salinity and Secondary Salinisationmentioning
confidence: 99%
“…While richness certainly responded to large changes in salinity, so that wetlands with the highest salinities (>100 g Lot) have particularly depauperate communities, most halophiles had broad salinity tolerances and subgroupings of the highly heterogeneous communities in more moderately saline wetlands were not obviously related to salinity per se. Timms (1993) and Williams (1981) also noted that many salt lake species occurred across broad ranges of salinity and that, while salinity was important, it was not sufficient by itself to explain much of the variation in salt lake communities. This idea was expanded upon by Williams et al (1990), who found a strong relationship between salinity and aquatic invertebrate community composition in wetlands when the full salinity spectrum was considered, but suggested that other (unidentified) biotic and abiotic variables were likely to be as important, or more important, within narrower ranges of salinity.…”
Section: Salinity and Secondary Salinisationmentioning
confidence: 99%
“…In this sense, ordination analysis identified a group of tolerant species (i. e. Berosus hispanicus, Rhantus suturalis and Sigara stagnalis), typical of habitats with high conductivity or salinity values (Arnold & Ormerod, 1997;Garrido & Munilla, 2008; www.intechopen.com Hansen, 1987;Martinoy et al, 2006). Different authors have identified salinity as the most important factor regulating species composition (Britton & Johnson, 1987;Cognetti & Maltagliati, 2000;Martinoy et al, 2006;Timms, 1993). Thus, the two samples with higher salinities (Vixán in spring and summer of 1998) appear separated from the rest of the samples of 1998 (Figure 7).…”
Section: Discussionmentioning
confidence: 94%